Aberrant methylation of placental development genes in chorionic villi of spontaneous abortions with trisomy 16 - О. Yu. Vasilyeva; E. N. Tolmacheva; A. E. Dmitriev; Ya. A. Darkova; E. A. Sazhenova; T. V. Nikitina; I. N. Lebedev; S. A. Vasilyev (Вавиловский журнал генетики и селекции)
In humans, aneuploidy is incompatible with the birth of healthy children and mainly leads to the death of embryos in the early stages of development in the first trimester of pregnancy. Trisomy 16 is the most common aneup loidy among spontaneous abortions of the first trimester of pregnancy. However, the mechanisms leading to the death of embryos with trisomy 16 remain insufficiently investigated. One of these potential mechanisms is abnormal placental development, including aberrant remodeling of spiral arteries. Spiral artery remodeling involves the migration of trophoblast cells into the maternal spiral arteries, replacing their endothelium and remodeling to ensure a stable embryonic nutrition and oxygen supply. This is a complex process which depends on many factors from both the embryo and the mother. We analyzed the methylation level of seven genes (ADORA2B, NPR3, PRDM1, PSG2, PHTLH, SV2C, and TICAM2) involved in placental development in the chorionic villi of spontaneous abortions with trisomy 16 (n = 14), compared with spontaneous abortions with a normal karyotype (n = 31) and the control group of induced abortions (n = 10). To obtain sequencing libraries, targeted amplification of individual gene regions using designed oligonucleot ide primers for bisulfite-converted DNA was used. The analysis was carried out using targeted bisulfite massive parallel sequencing. In the group of spontaneous abortions with trisomy 16, the level of methylation of the PRDM1 and PSG2 genes was significantly increased compared to induced abortions (p = 0.0004 and p = 0.0015, respectively). In the group of spontaneous abortions, there was no increase in the level of methylation of the PRDM1 and PSG2 genes, but the level of methylation of the ADORA2B gene was significantly increased compared to the induced abortions (p = 0.032). The results obtained indicate the potential mechanisms of the pathogenetic effect of trisomy 16 on the placental development with the participation of the studied  genes.